INCIDENCE OF THYMUS GLAND PATHOLOGY IN PATIENTS WITH MYASTHENIA GRAVIS (LITERATURE REVIEW) (World Bulletin of Public Health, 2022)
Myasthenia gravis is a severe progressive disease with an unpredictable course. It is based on the production of autoantibodies that prevent normal neuromuscular transmission due to blockade of acetylcholine receptors [1, 2]. This pathology was first described at the end of the 17th century by the British neurologist Thomas Willis: "...a woman gradually and temporarily lost the strength and ability to speak, until she became silent like a fish". Wilhelm Erb (German neurologist) and Samuel Goldflam (Polish neurologist) made a major contribution to the study of myasthenia gravis, describing in detail the clinical manifestations of the disease, which contributed to the origin of another name for myasthenia gravis - "Erb-Goldflam disease".
Keywords: myasthenia gravis; Erb-Goldflam disease; Hashimoto's thyroiditis; acetylcholine receptors